Trust-Mediated Technology Acceptance in Digital Payment: Educational Implications for Financial Literacy (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study investigated the mediating role of customer trust in linking perceived usefulness and ease of use to reuse intention among digital payment users, providing implications for financial technology education curriculum development. Method: A quantitative survey involving 600 Pospay users was conducted using seven-point Likert scale questionnaires. Structural Equation Modeling with Partial Least Squares (PLS-SEM) was employed for analysis with bootstrapping (5,000 resamples) to test direct and indirect effects. Results: Perceived usefulness most strongly influenced customer trust (β = 0.611, p < 0.001), followed by perceived ease of use (β = 0.359, p < 0.001). Customer trust significantly predicted reuse intention (β = 0.447, p < 0.001) and fully mediated both pathways. The model explained 86.8% of trust variance and 82% of reuse intention variance. Novelty: This research extends the Technology Acceptance Model by identifying trust as the key psychological mechanism linking perceived usefulness and ease of use to reuse intention. More importantly, it highlights a pedagogical shift in financial technology education by emphasizing that financial literacy programs should integrate trust-building competencies alongside technical operational skills.